The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00213-019-05295-z
|View full text |Cite
|
Sign up to set email alerts
|

Subjective responses to amphetamine in young adults with previous mood elevation experiences

Abstract: Rationale-One risk factor for alcohol and substance misuse is hypomanic experiences, or periods of mood elevation. Young people who report hypomanic states are more likely to develop bipolar disorder (BP), and BP and other mood disorders increase the risk of addiction. We recently reported that young adults with a history of mood elevation experience less subjective effects from a low dose of alcohol, which may be predictive of future alcohol use. The finding with alcohol raised the question of whether this da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…There is a large and reliable body of evidence that not all persons who are exposed to a substance develop SUD behaviors and substance-related consequences, and similarly that not all persons experience a substance in the same way. The outcomes in the present study are consistent with prior research that has examined individual variation in response for various drugs (Agrawal et al, 2022;Bieber et al, 2008;de Wit & Phillips, 2012;Do et al, 2018;Schepers et al, 2019), and expanded upon these studies by determining these effects are also evidently using behavioral economics. This study utilized subjective effects as a metric for assessing use because they were hypothesized to be well-understood and easily identifiable to the participants as well as something that could be assessed quickly and easily in a real-world setting, thus providing a potential rapid assessment of risk profile.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…There is a large and reliable body of evidence that not all persons who are exposed to a substance develop SUD behaviors and substance-related consequences, and similarly that not all persons experience a substance in the same way. The outcomes in the present study are consistent with prior research that has examined individual variation in response for various drugs (Agrawal et al, 2022;Bieber et al, 2008;de Wit & Phillips, 2012;Do et al, 2018;Schepers et al, 2019), and expanded upon these studies by determining these effects are also evidently using behavioral economics. This study utilized subjective effects as a metric for assessing use because they were hypothesized to be well-understood and easily identifiable to the participants as well as something that could be assessed quickly and easily in a real-world setting, thus providing a potential rapid assessment of risk profile.…”
Section: Discussionsupporting
confidence: 84%
“…Initial experience was also a more robust predictor than other traditional measures of alcohol use collected at the baseline visit (e.g., drinks per day, AUD checklist). Additional survey studies examining alcohol, cannabis, opioids, and tobacco use have also reported that only a subset of individuals experiences stimulating or otherwise rewarding effects to a given substance and that the severity of future use is positively associated with the presence of those effects (Agrawal et al, 2022; Bieber et al, 2008; de Wit & Phillips, 2012; Do et al, 2018; Schepers et al, 2019).…”
mentioning
confidence: 99%
“…Given the association between AUD and bipolar disorder, and between hypomania and hypersensitivity to reward ( O’Sullivan et al, 2011 ), an intuitive hypothesis is that a bipolar phenotype would be associated with enhanced sensitivity to the subjective effects of alcohol and other psychoactive drugs. However, in an acute challenge study with 0.8 g/kg alcohol, Yip et al (2012) reported reduced general sensitivity to alcohol in those with a history of hypomania, a pattern that was also found following acute amphetamine administration in a different study ( Schepers et al, 2019 ). As such, while some risk factors for AUD and substance use disorder (SUD; e.g., FH+) appear to be associated with enhanced subjective responses to certain psychoactive drugs, others (e.g., bipolar phenotype) are associated with reduced responses.…”
Section: Introductionmentioning
confidence: 87%
“…Although direct comparison of subjective effects of amphetamines in adolescent and adult humans is currently lacking in the literature, a more recent study (Schepers et al, 2019) examined the subjective effects of AMP in a specifically adolescent population (18-19 years old). Participants reported their subjective effects following oral intake of AMP within a therapeutic dose range (10 or 20 mg) or placebo.…”
Section: Laboratory Studies In Humansmentioning
confidence: 99%
“…An important distinction between these two studies is the ages of the participants. Mayo et al (2019) used participants ranging in age from 18-35 years old (average: 24.8), whereas Schepers et al (2019) had a smaller age range of 18-19 years old that is more specific to adolescence. Sex differences in the subjective response to amphetamines in humans may emerge during late adolescence or young adulthood, but this distinction is impossible to confirm without a direct comparison between separate groups of adolescents and adults.…”
Section: Laboratory Studies In Humansmentioning
confidence: 99%